2017
DOI: 10.1093/neuros/nyx312
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Treatment Response and Survival Outcomes in Meningioma Recurrence with Atypical or Anaplastic Histology

Abstract: Treatment of recurrent meningiomas with atypical/anaplastic histology remains challenging. Our data, from one of the largest cohorts, suggest better tumor control with the addition of radiation and challenges the importance of extent of resection at first recurrence. A multicenter effort is needed to confirm these findings and propose treatment guidelines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
21
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 69 publications
1
21
0
1
Order By: Relevance
“…A competitive risk regression model was used to analyze the predictors of second recurrence. These authors suggested increasing radiation therapy to better control the tumor and challenged the importance of the extent of resection in the first recurrence ( 32 ). Both above-described studies built a model and predicted the recurrence of meningiomas; however, compared to our study, these two previous studies included fewer patients, focused only on the risk factors and did not further quantify or classify the results.…”
Section: Discussionmentioning
confidence: 99%
“…A competitive risk regression model was used to analyze the predictors of second recurrence. These authors suggested increasing radiation therapy to better control the tumor and challenged the importance of the extent of resection in the first recurrence ( 32 ). Both above-described studies built a model and predicted the recurrence of meningiomas; however, compared to our study, these two previous studies included fewer patients, focused only on the risk factors and did not further quantify or classify the results.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, in patients with recurrent high‐grade meningioma, Cox regression analysis failed to identify any factor with significant association with either PFS or OS. However, the result from another retrospective study suggested better tumor control with the addition of radiation for patients with recurrent high‐grade meningioma . Thus, a larger cohort or multicenter clinical trial is needed to investigate the effect of radiation in this subgroup.…”
Section: Discussionmentioning
confidence: 99%
“…However, the result from another retrospective study suggested better tumor control with the addition of radiation for patients with recurrent high-grade meningioma. 21 Thus, a larger cohort or multicenter clinical trial is needed to investigate the effect of radiation in this subgroup. Adjuvant radiotherapy is generally recommended for patients with primary high-grade meningioma after incomplete resection, 6,7,10,22 with isolated reports suggesting that postoperative stereotactic radiosurgery is not associated with a statistically significant PFS benefit for patients with atypical meningioma following STR.…”
Section: Discussionmentioning
confidence: 99%
“…There have been a number of reports looking into factors associated with progression-free survival with multiple factors being implicated. Location, [ 10 , 32 ] extent of resection, [ 15 , 17 , 20 , 33 35 ] presence of atypia, [ 36 ] brain invasion, [ 23 , 26 , 37 , 38 ] high MI, [ 26 , 37 – 39 ] high MIB1 labelling, [ 15 , 17 , 33 , 39 ] bone involvement, [ 19 , 23 , 37 ] use of adjuvant radiotherapy [ 9 , 40 42 ] and secondary progression from WHO I tumour. [ 30 ] However, others have shown that none of the above factors influence the recurrence rate or time to recurrence of atypical meningioma.…”
Section: Discussionmentioning
confidence: 99%